Copper/Zinc-Modified Palygorskite Protects Against Salmonella Typhimurium Infection and Modulates the Intestinal Microbiota in Chickens - Zhang, Chaozheng; Yao, Dawei; Su, Zenan; Chen, Huan; Hao, Pan; Liao, Yun; Guo, Yiwen; Yang, Deji (Frontiers in Microbiology, 2021)
Palygorskite (Pal), a clay nanoparticle, has been demonstrated to be a vehicle for drug delivery. Copper has antibacterial properties and zinc is an essential micronutrient for intestinal health in animals and humans. However, whether copper/zinc-modified Pal (Cu/Zn-Pal) can protect chickens from Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) infection remains unclear. In this study, three complexes (Cu/Zn-Pal-1, -2 and -3) were prepared and Cu/Zn-Pal-1 was shown to be the most effective at inhibiting the growth of S. Typhimurium in vitro, whereas natural Pal alone had no inhibitory effect. In vivo, Cu/Zn-Pal-1 reduced S. Typhimurium colonization in the intestine of infected chickens and relieved S. Typhimurium-induced organ and intestinal mucosal barrier damage. Moreover, this reduction in Salmonella load attenuated intestinal inflammation and the oxidative stress response in challenged chickens. Additionally, Cu/Zn-Pal-1 modulated the intestinal microbiota in infected chickens, which was characterized by the reduced abundance of Firmicutes and the increased abundance of Proteobacteria and Bacteroidetes. Our results indicated that the Cu/Zn-Pal-1 complex may be an effective feed supplement for reducing S. Typhimurium colonization of the gut.